Respuesta :
Question :
- Solve 3 [-x + (2x + 1) ] = x - 1
Solution :
⇒ 3 [-x + 2x + 1] = x - 1
⇒ 3 [x + 1] = x - 1
⇒ 3 × [x + 1] = x - 1
⇒ 3x + 3 = x - 1
⇒ 3x - x + 3 = -1
⇒ 2x + 3 = -1
⇒ 2x = -1 - 3
⇒ 2x = -4
⇒ x = -4 / 2
⇒ x = -2
Simplifying
3[-1x + (2x + 1)] = x + -1
Reorder the terms:
- 3[-1x + (1 + 2x)] = x + -1
Remove parentheses around (1 + 2x)
- 3[-1x + 1 + 2x] = x + -1
Reorder the terms:
- 3[1 + -1x + 2x] = x + -1
Combine like terms: -1x + 2x = 1x
- 3[1 + 1x] = x + -1
- [1 * 3 + 1x * 3] = x + -1
- [3 + 3x] = x + -1
Reorder the terms:
- 3 + 3x = -1 + x
Solving
- 3 + 3x = -1 + x
Solving for the variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
- 3 + 3x + -1x = -1 + x + -1x
Combine like terms: 3x + -1x = 2x
- 3 + 2x = -1 + x + -1x
Combine like terms: x + -1x = 0
- 3 + 2x = -1 + 0
- 3 + 2x = -1
Add '-3' to each side of the equation.
3 + -3 + 2x = -1 + -3
Combine like terms: 3 + -3 = 0
- 0 + 2x = -1 + -3
- 2x = -1 + -3
Combine like terms: -1 + -3 = -4
- 2x = -4
Divide each side by '2'.
- x = -2
Simplifying
- x = -2